The effect of financial development and remittances on economic growth - Naqeeb-ur-Rehman; Eglantina Hysa (Cogent Economics & Finance, 2021)
The purpose of this study is to examine the effect of financial development and remittances on economic growth across six Western Balkan countries (WBC) using panel data from 2000 to 2017. Previous studies have neglected the effect of financial development and remittances on economic growth with regard to WBC. Based on system GMM analysis, we found that financial development (broad money stock ratio) and remittances shows positive impact on economic growth across WBC. However, the interaction of financial development and remittances provide a significant and negative effect on economic growth. The results imply that remittances together with financial development substitutes the economic growth of WBC. In order to expand the financial system in the WBC, policies targeted to develop the non-deposit financial institutions and using the narrow interest rate margin policy to encourage investment and thus high economic growth.
Keywords: 330; economic growth; financial development; remittances